Mechanism of proton-coupled quinone reduction in Photosystem II - Saito, Keisuke (National Academy of Sciences, 2013)
Photosystem II uses light to drive water oxidation and plastoquinone (PQ) reduction. PQ reduction involves two PQ cofactors, Q(A) and Q(B), working in series. Q(A) is a one-electron carrier, whereas Q(B) undergoes sequential reduction and protonation to form Q(B)H(2). Q(B)H(2) exchanges with PQ from the pool in the membrane. Based on the atomic coordinates of the Photosystem II crystal structure, we analyzed the proton transfer (PT) energetics adopting a quantum mechanical/molecular mechanical approach. The potential-energy profile suggests that the initial PT to Q(B)(•–) occurs from the protonated, D1-His252 to Q(B)(•)(–) via D1-Ser264. The second PT is likely to occur from D1-His215 to Q(B)H(−) via an H-bond with an energy profile with a single well, resulting in the formation of Q(B)H(2) and the D1-His215 anion. The pathway for reprotonation of D1-His215(–) may involve bicarbonate, D1-Tyr246 and water in the Q(B) site. Formate ligation to Fe(2+) did not significantly affect the protonation of reduced Q(B), suggesting that formate inhibits Q(B)H(2) release rather than its formation. The presence of carbonate rather than bicarbonate seems unlikely because the calculations showed that this greatly perturbed the potential of the nonheme iron, stabilizing the Fe(3+) state in the presence of Q(B)(•–), a situation not encountered experimentally. H-bonding from D1-Tyr246 and D2-Tyr244 to the bicarbonate ligand of the nonheme iron contributes to the stability of the semiquinones. A detailed mechanistic model for Q(B) reduction is presented.